The impact of osteoarthritis on early exit from work - Laires, Pedro A (2018)
BACKGROUND: Osteoarthritis (OA) is a leading cause of pain and disability, which may be a source of productivity losses. The objectives of this study were to describe the impact of OA, namely through pain and physical disability, on early exit from work and to calculate its economic burden. METHODS: We analysed data from the national, cross-sectional, population-based EpiReumaPt study (Sep2011-Dec2013) in which 10,661 individuals were randomly surveyed in order to capture all cases of rheumatic diseases. We used all participants aged 50-64, near the official retirement age, who were clinically validated by experienced rheumatologists (n = 1286), including OA cases. A national database was used to calculate productivity values by gender, age and region, using the human capital approach. The impact of OA on the likelihood of early exit from work and the population attributable fractions used to calculate due economic burden (indirect costs) were obtained at the individual level by logistic regression. All results were based on weighted data. RESULTS: Almost one third of the Portuguese population aged 50-64 had OA (29.7%; men: 16.2% and women: 43.5%) and more than half were out of paid work (51.8%). Only knee OA is associated with early exit from work (OR: 2.25; 95%CI: 1.42-3.59; p = 0.001), whereas other OA locations did not reach any statistical difference. Furthermore, we observed an association between self-reported longstanding musculoskeletal pain (OR: 1.55; 95%CI: 1.07-2.23; p = 0.02) and pain interference (OR: 1.35; 95%CI: 1.13-1.62; p = 0.001) with early exit from work. We also detected a clear relationship between levels of disability, measured by the Health Assessment Questionnaire (HAQ), and the probability of work withdrawal. The estimated annual cost of early exit from work attributable to OA was €656 million (€384 per capita; €1294 per OA patient and €2095 per OA patient out-of-work). CONCLUSIONS: In this study, we observed an association between OA and early exit from work, largely dependent on pain and disability. This relationship translates into a meaningful economic burden amounting to approximately 0.4% of the national Gross Domestic Product (GDP). The high prevalence and the impact of this disabling chronic disease highlight the need to prioritize policies targeting early exit from work in OA.